Participatory Action Research: Strategies for Implementation in Counseling Outcome Research. Issue 1 (2nd January 2022) - Speedlin, Stacy; Haberstroh, Shane; Townsend, Christopher; Prasath, Priscilla; McVay, Katherine
ABSTRACT: Participatory action research (PAR) is an innovative research methodology grounded in collaboration and aimed creating systemic and social change. PAR scholars honor and recognize power inequities, culturally centred change, and the robust and equitable collaboration between research participants and formal investigators. In this paper, we explore the use of PAR as a methodology for counseling research that is practice based and accessible to researchers and counselors who desire to implement relatively rapid changes to counseling programs and practices. Finally, we discuss potential issues that may arise with PAR and provide solutions for resolving dilemmas.